Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Taylor Series Problems Help??

Help me!

Attachment image

3 Answers

Relevance
  • cidyah
    Lv 7
    3 years ago

    6)

    f(x)= x^(-1)

    f(1) = 1

    f'(x) = (-1)x^(-2) = -1/x^2

    f'(1) = -1

    f''(x) = (-1)(-2)x^(-3) = 2/x^3

    f''(1) = 2

    f(x) = f(1) +(x-1) f'(1) + (x-1)^2 f''(1) / 2!

    f(x) = 1 +(x-1)(-1) + (x-1)^2 (2)/(2!)

    f(x) = 1 +1-x +(x^2-2x+1)

    f(x) = x^2-3x+3

    2)

    f(x) = 3 + x + x^2

    f(1) = 5

    f'(x) = 1+2x

    f'(1) = 3

    f''(x) = 2

    f''(1) = 2

    f(x) = f(1) + (x-1) f'(1) +(x-1)^2 f''(1) /2!

    f(x) = 5 +(x-1)(3) + (x-1)^2 (2/2)

    f(x) = 5 +3x-3 +x^2-2x+1

    f(x) = x^2+x+3

    3)

    f(x) = cos(2x)

    f(pi) = cos(pi) = -1

    f'(x) = -2sin(2x)

    f'(pi) = 0

    f''(x) = -4 cos(2x)

    f''(pi) = -4 cos(2pi) = -4(1) = -4

    f(x) = f(pi) + (x-pi) f'(pi) +(x-pi)^2 f''(pi) /2!

    f(x) = -1 + (x-pi) (0) + (x-pi)^2 (-4/2)

    f(x) = -1 -2 (x-pi)^2

    4)

    f(x)=sqrt(x)

    f(4) = 2

    f(x) = x^(1/2)

    f'(x) = (1/2) x^(-1/2) = 1/(2x^(1/2)) = 1/(2sqrt(x))

    f'(4) = 1/(2sqrt(4)) = 1/((2)(2)) = 1/4

    f''(x) = (1/2)(-1/2) x^(-3/2) = -1/(4x^(3/2))

    f''(4) = -1/(4 (4)^(3/2)) = -1/32

    f(x) = f(4)+(x-4)f'(4) +(x-4)^2 f''(4)/2!

    f(x) = 2 + (x-4) (1/4) + (x-4)^2 (-1/32)(1/2!)

    f(x) = 2 + (1/4) x -1 +(x^2-8x+16)(-1/64)

    f(x) = (-1/64)x^2 +x(1/4 +1/8) +2-1-1/4

    f(x) = (1/64)x^2 +(3/8)x +3/4

  • General form of the Taylor Series:

    f(a) * (x - a)^0 / 0! + f'(a) * (x - a)^1 / 1! + f''(a) * (x - a)^2 / 2! + f[3](a) * (x - a)^3 / 3! + .... + f[n](a) * (x - a)^n / n!

    For instance, problem number 5

    f(x) = 2 * cos(x)

    a = pi/2

    f(a) = 2 * cos(pi/2) = 2 * 0 = 0

    f'(a) = -2 * sin(pi/2) = -2 * 1 = -2

    f''(a) = -2 * cos(pi/2) = -2 * 0 = 0

    f'''(a) = 2 * sin(pi/2) = 2 * 1 = 2

    And it will repeat

    0 + (-2) * (x - pi/2) / 1! + 0 * (x - pi/2)^2 / 2! + 2 * (x - pi/2)^3 / 3! + 0 * (x - pi/2)^4 / 4! + ..... =>

    -2 * (x - pi/2) + 2 * (x - pi/2)^3 / 3! - 2 * (x - pi/2)^5 / 5! + 2 * (x - pi/2)^7 / 7! + .... =>

    2 * (-1) * (x - pi/2) + 2 * (-1)^2 * (x - pi/2)^3 / 3! + 2 * (-1)^3 * (x - pi/2)^5 / 5! + 2 * (-1)^4 * (x - pi/2)^7 / 7! + ...

    The infinite sum of: 2 * (-1)^n * (x - pi/2)^(2n - 1) / (2n - 1)! from n = 1 to n = infinity

  • ?
    Lv 7
    3 years ago

    Valuable advice: Its impolite to ask several questions per post. Ask just one per post. And ask one at a time & learn from it. Only then if u still need help, ask for further clarification.

Still have questions? Get your answers by asking now.